Analisis Ekonomi dan Kebijakan Pengembangan Energi Arus Laut di Selat Madura, Provinsi Jawa Timur - Adil Mahfudz Firdaus; Tridoyo Kusumastanto; I Wayan Nurjaya (STI Policy and Management Journal, 2015)
The increasing of energy use will lead to depletion of fossil energy resources, therefore it is important to develop a renewable energy sources. Ocean currents energy is one of renewable energy which can develop to fulfil high energy demands, especially for electricity needs. Ocean currents energy development needs to be supported by appropriate technologies and policies. In addition, public perceptions on renewable energy also needs to be considered. The economics based on community and economic sectors approach have not been fully studied. Therefore, this paper examines the potential of ocean currents energy development based on economics studies and policy approach. Based on research, Madura Strait has sufficient resource potential to produce energy. WTP analysis showed respondents afford to pay higher electricity amounting to IDR 486,38 kwh. The electricity and gas sector has contributed 1,28 percent after investment injection of 3 MW ocean currents power plant to East Java Province’s GRDP 2012. Assessment policy analysis showed infrastructure of power plant as a policy priority in the development of ocean currents energy.